Classification of the correct Quranic letters pronunciation of male and female reciters - Khairuddin, Safiah; Ahmad, Salmiah; Embong, Abd Halim; Nik Hashim, Nik Nur Wahidah; Altamas, Tareq M.K.; Syd Badaruddin, Syarifah Nuratikah; Hassan, Surul Shahbudin (IOP Publishing, 2017)
Recitation of the Holy Quran with the correct Tajweed is essential for every Muslim. Islam has encouraged Quranic education since early age as the recitation of the Quran correctly will represent the correct meaning of the words of Allah. It is important to recite the Quranic verses according to its characteristics (sifaat) and from its point of articulations (makhraj). This paper presents the identification and classification analysis of Quranic letters pronunciation for both male and female reciters, to obtain the unique representation of each letter by male as compared to female expert reciters. Linear Discriminant Analysis (LDA) was used as the classifier to classify the data with Formants and Power Spectral Density (PSD) as the acoustic features. The result shows that linear classifier of PSD with band 1 and band 2 power spectral combinations gives a high percentage of classification accuracy for most of the Quranic letters. It is also shown that the pronunciation by male reciters gives better result in the classification of the Quranic letters.